Ergebnisse der Albanien-Expedition 1961 des Deutschen Entomologischen Institutes. 23. Beitrag: Raphidioptera. - Bartoš, Emanuel (Contributions to Entomology = Beiträge zur Entomologie, 1964)
The author gives the results of his investigations on Raphidioptera of Albania. The material collected by the Albania-Expedition of the Deutsches Entomologisches Institut contained only 5 specimens of the Raphidioptera, which belong to 2 species and 1 variety. One of them is new to the fauna of Albania. Together there are known 2 species from Albania now.